Analysis of the Assaults Associated with Stab Wounds Ten Year Experience in Manisa - Yavuz, Mehmet Sunay; Aşırdizer, Mahmut; Tuyji, Yeşim; Zeyfeoğlu, Yıldıray; Dizdar, Mustafa Gökhan; Uluçay, Tarık (The Bulletin of Legal Medicine, 2011)
Although stab wounds associated with interpersonal violence are accepted as one of major problems in many countries, their incidence in Turkey has not been determined yet. The aims of this study were: to analyze the incidents associated with stab wounds and features of victims and offenders; to compare with previously reported data; and to identify preventive measures appropriate for Turkey. Two hundred and thirty eight cases of assault by stab were evaluated in Forensic Medicine Outpatient Clinic of Celal Bayar University Hospital between 2002 and 2012. Most of the victims and offenders were males (94.5%; 96.5%, respectively) aged between 20-39 years (60.1%; 67.3%, respectively). Most of stab wounds were inflicted by knives/penknives (81%). Assaults mostly occurred on streets (40.3%) and public areas (36.2%) and during night hours (31.1%). Most ofthe injuries were soft tissue injuries (73.8%) and the most commonly affected structures were intrathoracic organs and/or vessels (40.8%). Ofthe victims 37.4% were exposed to life-threatening acts, while 21% of them sustained various sequels. The actual solution of assaults associated with stab wounds in the control of crime prevention involves educational, socio-cultural and economic efforts; enforcing the legislations against carrying knives and increasing police controls in streets and public places, especially in nights.Key words: Violence, wounds, stab, crime, forensic medicine
Keywords: violence; wounds; stab; crime; forensic medicine